Predictive value of novel nutritional inflammation indexes in IVIG-unresponsive Kawasaki disease: a retrospective study - Yi, Cong; Xue, Dan; Chen, Jia; Guo, Jun; Zhou, Yu-Neng; Hu, Yu; She, Xiang (Frontiers in Nutrition, 2025)
ObjectiveThis retrospective study aimed to investigate the predictive value of novel albumin-associated nutritional inflammation markers, including the C-reactive protein-albumin-lymphocyte (CALLY) index, C-reactive protein to albumin ratio (CAR), neutrophil-to-albumin ratio (NAR), neutrophil percentage-to-albumin ratio (NPAR) and prognostic nutritional index (PNI), for intravenous immunoglobulin (IVIG) resistance in Kawasaki disease (KD) patients.MethodsWe conducted a retrospective analysis of clinical data from pediatric patients diagnosed with KD and admitted to our hospital between January 2012 and November 2023. Data were analyzed using univariate analysis, binary logistic regression analysis, and receiver operating curve (ROC) analysis.ResultsThe study included 716 children with KD, and 78 of them (10.9%) were diagnosed with IVIG-resistant KD. CAR, NAR and NPAR were positively correlated with IVIG resistance, while the CALLY index and PNI showed negative correlations. The area under the ROC curve (AUC) values of the CALLY index, CAR, NAR, NPAR and PNI were 0.725, 0.700, 0.580, 0.717 and 0.712.ConclusionOur findings suggest that these novel nutritional inflammation indexes could be useful tools for predicting IVIG resistance in KD patients, potentially guiding timely intensified therapy. Compared to NAR, the CALLY index, CAR, NPAR, and PNI demonstrate stronger predictive performance for intravenous immunoglobulin (IVIG) resistance in Kawasaki disease and may hold greater potential for clinical application.